Strategi Dan Analisis Risiko Dalam Manajemen Investasi Modern - Galih thoriq murdianto; Ferry Khoirul Fadillah; Japar Arofik; Pupung Purnamasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Modern investment management requires a strategic approach that is able to adapt to the increasingly complex and volatile market dynamics. This study aims to examine various contemporary investment strategies and risk analysis methods that are applied in optimal portfolio management. Through a review of literature and secondary data analysis, this study evaluates the effectiveness of strategies such as asset diversification, the use of algorithm -based technology, and quantitative approaches in minimizing risk and maximizing yield. In addition, this study also discussed the application of systematic risk models such as Value at Risk (VAR), Monte Carlo Simulation, and the Behavioral Finance approach as a response to market uncertainty. The results of the study show that the integration between proactive risk management and adaptive investment strategies play an important role in creating portfolio stability, especially in the context of digital economy development. These findings have practical implications for investors, asset managers, and policy makers in designing investment decisions that are more responsive to changes in the financial environment.